Potential Bacterial Antagonists for the Control of Charcoal Rot (Macrophomina phaseolina) in Strawberry - Viejobueno, Josefina (2021)
The effect of antagonistic bacteria to control Macrophomina phaseolina was evaluated under in vitro, growth chamber, greenhouse and field conditions. A total of 177 bacteria, isolated from Athrocaulon macrostachyum rhizosphere of the Lebrija marsh, were screened for their potential against M. phaseolina (causes charcoal rot in strawberry) by dual culture assay. Of these isolates, 14 most promising strains were molecularly identified by the 16S rDNA sequencing method using the EzBioCloud database. These strains were tested for in vitro hydrolytic enzymes, HCN production, and biocontrol against M. phaseolina in strawberry plants. All the 14 strains produced, at least, one hydrolytic enzymatic activity and one of them, which belongs to Brevibacterium genus (Hvs8), showed the lowest records of disease incidence (20%) and severity (0.4). With these results, greenhouse and field trials were carried out with the Hvs8 strain, compared to non-treated control. In the greenhouse assays, Hvs8 strain increased root dry mass by 30%, over the control. In the field trials, production and fruit quality were not significantly different between Hvs8 treatment and non-treated control, but plant mortality and plant mortality associated to M. phaseolina decreased by more than 24% and 65% respectively, in Hvs8 treatment. This study suggests that Brevibacterium sp. Hvs8 strain could be a candidate for controlling charcoal rot in strawberry.